Experiencing Life as Cinematic Fiction: The Marvelous within the Daily Media Landscape (AOQU (Achilles Orlando Quixote Ulysses). Journal on Epic, 2021)
Daily, we enter and exit several digital realms which dramatically overlap with our physical reality. Our identity is scattered in a multitude of customized characters, explicitly created to represent the fragments of our personality. However, up to what extent are we aware of all this? By applying Torquato Tasso’s notion of “marvelous” as a revelatory element, that is, «a process that provides access to a hidden dimension beyond reality» (Ardissino 2019), this essay aims at analyzing Monomyth: gaiden (2018-2020), a four parts animated series by Petra Széman, a Hungarian moving image artist. Széman uses the hero’s journey trope and the principles of the gaiden, a nonlinear narrative used in manga and anime, to investigate the discrepancies occurring at the spectator-screen nexus «when journeying through an elusive multiplanar reality» (Széman 2018). Traveling between the fictional and the real world, Széman creates a digital épos which investigates «how the encounter between the human perceptual system and its media environment» (Levitt 2018) interacts in an interwoven network of virtual realms and non-localized identities.
Keywords: monomyth; heroe's journey; gaiden; marvelous; fiction; digital épos; media landscape; identity; transmedia storytelling